Kegiatan Gotong Royong Dan Kebersihan Lingkungan Dalam Rangka Mrensejahterakan Masyarakat Di Kelurahan Pematang Gubernur Kecamatan Pematang Gubernur RT. 25 RW.05 Kota Bengkulu - Rutiningsih, Ratna; Efendi , M. Aldi Rizki; Devalya, Devalya; Anderstar , Tomi; Radili , Putri; Effendi, Yanto; Fitriano, Yun; Susanti, Neri (Jurnal Karya Nyata Pengabdian, 2025)
It This study aims to analyze the impact of community service activities, particularly mutual cooperation (gotong royong) and environmental cleanliness, on the welfare of the community in Pematang Gubernur Village, Pematang Gubernur District, RT.25 RW.05, Bengkulu City. The research employs a qualitative approach, utilizing interviews, observations, and documentation as data collection methods. The findings indicate that gotong royong activities significantly enhance community engagement, improve environmental conditions, and foster a sense of belonging among residents. The study concludes that regular community service initiatives are essential for promoting social welfare and environmental sustainability.